Different age, different blood parasites - Acrocephalus species and their haemosporidian parasites during autumn migration in Central Europe - Nóra Ágh; Szilvia Pásztory-Kovács; Viola Prohászka; Tibor Csörgő; Eszter Szöllősi (International Journal for Parasitology: Parasites and Wildlife)
In migratory passerines, the timing of the different phases of the migratory journey is of great importance for the survival prospect of the individuals. Haemosporidian infections could weaken the immune system, decelerate the ability of fat accumulation and potentially influence the migratory behaviour. As a large number of blood parasites is host-generalist there is a potential for cross-species and cross-population transmission with different parasite species during the migratory route of the passerines. In addition, resident birds also interact with different parasite fauna when migratory birds arrive back from their migratory route, therefore, it is important to study what kind of blood parasites migratory birds carry.We screened three long-distant migratory Acrocephalus species during autumn migration in two years. We found that in reed and sedge warblers the overall prevalence of blood parasites was significantly higher in adults than in juveniles, and the prevalence of Haemoproteus infections was higher than that of the Plasmodium in adults. In contrast, Plasmodium infections dominated in juveniles in all the three species. The odds of catching infected juvenile individuals increased during the autumn migration, but infections had no significant effect on the actual body mass of the birds. These results could imply age-related differences in the probability of getting infected with different blood parasite genera. Sampling during migration and exploring the potential differences in parasite species composition and their effects on the migratory behaviour in different age groups can provide valuable insight in answering these questions.